Políticas públicas frente à inclusão da população LGBTQIA+ no ambiente formal do trabalho - Friedrich Júnior, Fernando Mogart (My University, 2024)
This final paper analyzes the public policies that aim at the inclusion of the LGBTQIA+ population in the formal work market. The initial discussion topic of the present work will revolve around the historical construction of the LGBTQIA+ (Lesbians, Gays, Bisexuals, Transexuals, Travestites, Queer, Intersex, Asexual plus) movement, an essential subject for understanding the relevance of the problems within this community. Then, the educational background of the LGBTQIA+ population will be analyzed in the contexts of elementary, secondary and university education, in order to identify obstacles that may be present when entering and staying in the formal job market. After understanding the stigmas and prejudices suffered by this minority group, the final discussion will be about public policies that could be implemented in order to fight the discrimination related to sexual orientation and gender identity. The method of bibliographic research and the analysis of the current legislation were used in order to achieve the objective. [resumo fornecido pelo autor]
O presente trabalho de conclusão de curso tem o objetivo de analisar as políticas públicas voltadas à inclusão da população LGBTQIA+ no ambiente formal do trabalho. Assim, inicialmente aborda-se a construção histórica do movimento LGBTQIA+ (Lésbicas, Gays, Bissexuais, Transexuais e Travestis, Queer, Intersexuais, Assexuais), título imprescindível para compreensão da relevância da problemática. Em seguida, será analisada a formação educacional da população LGBTQIA+ no âmbito do ensino fundamental, médio e superior, buscando identificar os possíveis obstáculos para o ingresso e permanência no mercado formal de trabalho. Por fim, compreendendo os estigmas e preconceitos sofridos por esse grupo minorizado, será discorrido acerca das políticas públicas que poderiam ser implementadas com o intuito de combater a discriminação relacionada à orientação sexual e identidade de gênero. Para atingir o fim almejado, foi utilizado o método de pesquisa bibliográfica e de legislações vigentes. [resumo fornecido pelo autor]
Keywords: Política pública (Direito); Homofobia; Mercado de trabalho; Minorias sexuais; Qualificações profissionais; Homossexualidade no ambiente de trabalho